2008
DOI: 10.1051/0004-6361:200809544
|View full text |Cite
|
Sign up to set email alerts
|

SOHO/SUMER observations of prominence oscillation before eruption

Abstract: Context. Coronal mass ejections (CMEs), as a large-scale eruptive phenomenon, often reveal some precursors in the initiation phase, e.g., X-ray brightening, filament darkening, etc., which are useful for CME modelling and space weather forecasting. Aims. With the Solar Ultraviolet Measurements of Emitted Radiation (SUMER) spectroscopic observations of the 2000 September 26 CME, we propose another precursor for CMEs, namely, long-time prominence oscillations. Methods. We observed the prominence oscillation-and-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 36 publications
6
74
0
5
Order By: Relevance
“…Since only one thread of the prominence was seen to erupt with the major part remaining in the low corona, this should be a partial prominence eruption event, which might be consistent with the rupture model (Sturrock et al 2001), where part of the flux rope struggle out of the overlying field lines, pushing some of them aside on the way, as simulated by Fan (2005). This paper might provide another example to illustrate that long-time prominence oscillation can be regarded as a precursor for CME eruptions, as proposed by Chen et al (2008). However, the eruption in this paper is different from theirs in the sense that their prominence oscillation was transverse, whereas ours is along the prominence axis, i.e., it is a longitudinal oscillation, although both of the prominence oscillations were probably triggered by magnetic reconnection between emerging flux and the pre-existing field lines.…”
Section: Possible Connection With the Later Cme/flaresupporting
confidence: 72%
See 2 more Smart Citations
“…Since only one thread of the prominence was seen to erupt with the major part remaining in the low corona, this should be a partial prominence eruption event, which might be consistent with the rupture model (Sturrock et al 2001), where part of the flux rope struggle out of the overlying field lines, pushing some of them aside on the way, as simulated by Fan (2005). This paper might provide another example to illustrate that long-time prominence oscillation can be regarded as a precursor for CME eruptions, as proposed by Chen et al (2008). However, the eruption in this paper is different from theirs in the sense that their prominence oscillation was transverse, whereas ours is along the prominence axis, i.e., it is a longitudinal oscillation, although both of the prominence oscillations were probably triggered by magnetic reconnection between emerging flux and the pre-existing field lines.…”
Section: Possible Connection With the Later Cme/flaresupporting
confidence: 72%
“…With the main body of the prominence remaining undisturbed, a thread from the prominence was seen to erupt, leading to a CME and a C1.2-class flare. We tentatively propose that the prominence longitudinal oscillations studied in this paper might be a precursor of the CME/flare, which is related to the triggering process of the eruption, as proposed by Chen et al (2008).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The exciter of prominence oscillations does not seem to be related to flares or other activity that was reported before (e.g. Jing et al 2003;Okamoto et al 2004;Isobe & Tripathi 2006;Isobe et al 2007;Xu et al 2008;Chen et al 2008). It is generally thought that the thread oscillations stem from magnetoacoustic waves (e.g.…”
Section: Conclusion and Discussionmentioning
confidence: 80%
“…SOHO/SUMER observations of a prominence oscillation were discussed in the context of the physics of CMEs (Chen et al 2008). It was suggested that repetitive reconnections between emerging flux and the pre-existing magnetic field are the trigger mechanism of Doppler velocity oscillations leading to the eruption.…”
Section: Introductionmentioning
confidence: 99%